Comparison of step-by-step kinematics and muscle activation of resisted, assisted, and unloaded 30-m sprints in sprinters - van den Tillaar, R.; Gamble, P. (Translational Sports Medicine, 2018)
The aim of this study was to compare step-by-step kinematics and muscle activation during 30-m sprint efforts under resisted, normal, and assisted conditions in experienced sprinters. Sixteen subjects performed resisted, normal, and assisted 30-m sprint in one session. Almost all measured kinematics were affected by resisted and assisted sprint conditions. The exception was that step frequency did not show any marked differences between the assisted sprint condition and normal sprints. Maximal angular velocity of hip flexion and knee extension increased the first four strides during all conditions, and muscle activation of the hamstrings muscles similarly increased with each of the first four strides. The only difference between conditions was that maximal knee extension velocity was reduced during the resisted condition. Step-by-step changes in muscle activation during the sprints also did not differ between conditions. It was concluded that the subjects were simply not able to increase limb velocity to the degree required to achieve greater step frequency under the assisted sprint condition as shown by similar maximal angular hip flexion, knee extension, and muscle activations. Furthermore, that the hamstrings muscles during acceleration are getting more important for propulsion than the other muscles, which are not changing much in activation.